Impacts of scaling up water recycling and rainwater harvesting technologies on hydraulic and hydrological flows - Bertrand, Nathalie Marie-Ange (Cranfield University, 2008)
In recent years, the increasing awareness of scarcity of water resources, indications of likely climate variability, and the increasing pressure to use available fresh water resources more efficiently have together reinforced the need to look at infrastructure solutions with due regard to environmental considerations and social impacts, present and future. There is a vital need to apply an integrated approach to catchment management to implement sustainable solutions to resolve issues such as water supply and sewerage, drainage and river flooding. Many potentials solutions are available to control water demand and manage flood problems. Greywater recycling and rainwater harvesting are novel technologies. However, their catchment scale impacts on hydraulic and hydrological flows are poorly understood. The research aim is to identify the hydrologic and hydraulic impacts of scaling up such technologies at catchment scale. For this particular study, a computer simulation model will be used to evaluate how increasing urbanisation, climate change and the implementation of greywater recycling and rainwater harvesting may alter the water balance within a representative catchment. To achieve these aims data from the Carrickmines catchment in Ireland have been collected; a simulation model has been adapted to carry out the study, the model has been calibrated and validated, results have been analysed, and finally, a sensitivity analysis has been carried out. The results show that rainwater harvesting systems are comparatively more effective than greywater recycling techniques in reducing flood frequency and intensity. Under five year return period rainfall events, the implementation of rainwater harvesting at any scale and number of units is a useful technique to control river flow and floods. However, the study also shows that under extreme conditions the efficiency of rainwater harvesting systems decreases. The study concludes that implementing the two technologies within a single catchment is not a solution to several forms of hydrological problem. The study shows that implementing rainwater harvesting or re-use technologies are a very useful way to protect local freshwater reserves and therefore conserve our environment.
Keywords: Water network modelling; greywater recycling; rainwater harvesting systems; Water management; catchment scale